Relationship between Thrombosis Risk Factors, Clinical Symptoms, and Laboratory Findings with Pulmonary Embolism Diagnosis; a Cross-Sectional Study - Bozorgmehr, Rama; Pishgahi, Mehdi; Mohaghegh, Pegah; Bayat, Marziye; Khodadadi, Parastou; Ghafori, Ahmadreza (Archives of Academic Emergency Medicine, 2019)
Introduction: Pulmonary embolism (PE) is a potentially life threatening disease, accurate and timely diagnosis of which is still a challenge that physicians face. This study was designed with the aim of evaluating the relationship between thrombosis risk factors, clinical symptoms, and laboratory findings with the presence or absence of PE. Methods: The present retrospective cross-sectional study was performed on patients with suspected pulmonary embolism who were hospitalized in different departments of Shohadaye Tajrish Hospital, Tehran, Iran, during 1 year. All patients underwent computed tomography pulmonary angiography (CTPA) and then thrombosis risk factors, clinical symptoms, and laboratory findings of confirmed PE cases with CTPA were compared with others. Results: 188 patients with the mean age of 61.91 Â± 18.25 (20 â€“ 101) years were studied (54.8% male). Based on Wells’ score, 32 (17.2%) patients were in the low risk group, 145 (78.0%) were in the moderate risk group, and 9 (4.8%) patients were classified in the high risk group for developing PE. CTPA findings confirmed PE diagnosis for 60 (31.7%) patients (6.7% high risk, 75.0% moderate risk, 18.3% low risk). D-dimer test was only ordered for 27 patients, 25 (92.6%) of which were positive. Among the patients with positive D-dimer, 18 (72.0%) cases had negative CTPA. Inactivity (57.4%), hypertension (32.8%), and history of cancer (29.5%) were the most common risk factors of thrombosis in patients with PE. In addition, shortness of breath (60.1%) and tachypnea (11.1%) were the most common clinical findings among patients with PE. There was no significant difference between the patients with PE diagnosis and others regarding mean age (p = 0.560), sex distribution (p = 0.438), and type of thrombosis risk factors (p > 0.05), hospitalization department (p = 0.757), Wellsâ€™ score (p = 0.665), electrocardiography findings, or blood gas analyses. Conclusion: Although attention to thrombosis risk factors, clinical symptoms, and laboratory findings, can be helpful in screening patients with suspected PE, considering the ability of CT scan in confirming or ruling out other possible differential diagnoses, it seems that a revision should be done to lower the threshold of ordering this diagnostic modality for suspected cases.